Dançando com a diversidade - Lopes, Luana Rachel de Araújo (2019)
It is notable the demands and the inquiries about the autism that is still a unknown field for educators and family. The spectrum has diverge degrees and an infinity of symptoms that become different for each unity as organism. The syndrome can show up in the first years of the life and we do not know the causes and their origin, because its appearance is a complex, wich can delay its early diagnosis, and presents several behavioral frameworks, such as the inability in the interpersonal relationship, delay in acquisition of the speech and motor difficulties. In relation to social and education living, we have the LDB 9.394/96 used as a legal device that the available regular teaching defends for learners with global developmental disorders, so that the autistic persons have access to the school and can develop social and intellectual skills in accordance with his limits. The objective of this study is to verify the possibilities of experiencing dance in an inclusive perspective with students how dance contents can be applied and what type of strategies could be used. So, we realized a literature review was elaborated to which several authors discuss the importance of inclusive dance for the development of students with ASD (Autism Spectrum Disorder). In this dialogue it is concluded that the dance is a powerful tool that transforms the routine into a dialogue between the individual and the external environment and even with the people who share this space. The schools need to invest in dance experiences in order to establish communication, trying to effect a relationship with the external environment and with the people who are part of it. To dance is to learn to experience, to recognize oneself as a power. To discover without imposed rules and to dialogue with the world in double way, interpreting the propositions that are given to us and saying yes to the diversities.